Lepeophtheirus cuneifer sp. nov. (Copepoda: Caligidae), a Parasite of Fishes from the Pacific Coast of North America - Kabata, Z. (Journal of the Fisheries Research Board of Canada, 1974)
Lepeophtheirus cuneifer sp. nov. (Copepoda: Caligidae) is described and illustrated. This copepod is a parasite of marine fishes off the coast of Alaska, its hosts including Raja binoculata and Hexagrammos lagocephalus. Other possible hosts are Leptocottus armatus and Theragra chalcogramma.